A dynamic trust evaluation scheme for cooperative spectrum sensing - Meiying WANG; Jingyu FENG; Guangyue LU; Dingkun HAN (Dianxin kexue)
Considering the harmful effect of dynamic SSDF attack against cooperative spectrum sensing technologies，a dynamic trust evaluation scheme based on the real-time observation and analysis of cognitive users’ sensing behaviors was proposed.Time attenuation，additive reward and additive penalty factors based on the historical sensing variation of cognitive users were introduced to calculate the dynamic trust value which changes with time and the number of collaborations.Meanwhile，trusted cognitive users were selected to participate in cooperative sensing，and thus improving the accuracy of the final sensing decision.Simulation results show that the scheme can effectively suppress the growth of trust of malicious users，and reduce the attack success rate for“OR”，“AND”and“Majority”which are three kinds of cooperative spectrum sensing data fusion schemes.